STRATEGI PEMASARAN PRODUK CICIL EMAS BERBASIS AKAD MURABAHAH PADA LEMBAGA KEUANGAN SYARIAH: STUDI KASUS BANK X - Entaresmen, R. ajeng; Windhy Puspitasari; Defita Fitrianingsih (Media Ekonomi, 2024)
Gold installment financing is an investment-oriented financial product that allows customers to acquire gold through a structured payment plan. Gold is considered a resilient and promising asset, offering significant advantages as it tends to maintain its value over time and is not susceptible to inflationary pressures—unlike savings held in cash, which depreciate in value due to inflation. Consequently, gold saving emerges as a highly competitive and strategic financial choice. The relatively stable resale value of gold, which often does not significantly deviate from its initial purchase price, enhances its attractiveness as an investment vehicle. This study aims to: (1) examine the implementation of the murabahah contract in the marketing strategy of gold installment products for increasing customer acquisition (a case study at Bank X); and (2) analyze strategic factors through a SWOT framework, strengths, weaknesses, opportunities, and threats, in the promotion of these products using murabahah contracts. This research adopts a qualitative approach aimed at developing a comprehensive understanding of the phenomena as perceived by research participants, including behaviors, perceptions, motivations, and actions, within a natural setting, and through descriptive narratives expressed in verbal form. Data were analyzed using SWOT analysis. The findings indicate that the gold installment financing scheme using the murabahah contract at Bank X is a facility developed by PT X, and has successfully engaged with cooperatives, institutions, and Islamic financial entities. These partnerships represent valuable assets that should be continuously nurtured and maintained to support sustainable customer growth